Organizational and Economic Mechanism of Services Spheres Innovative Development Maintenance as a Component of Management of Regional Economy - Pavlova, Adeliya V.; Novikova, Anna V.; Pogulich, Oksana V.; Chudnovskiy, Alexey D.; Zakirova, Chulpan S.; Kaptelinina, Elena A.; Gafurova, Alfira Y.; Matveeva, Elena S. (International Review of Management and Marketing, 2016)
The relevance of the study is conditioned by innovative development of services spheres by improving their competitiveness, investment attractiveness and growth of the objectively existing advantages of regions, reducing the cost of doing business. Services sphere is one of the most dynamic and fastest-growing segments of the regional markets, as well as one of the characteristics of the effectiveness of social and economic policy in the region. The growth of the profitability through the services spheres’ assets while diversifying risk, aimed at innovative development of services spheres, meeting the needs of the population in public goods and improving of life quality provides a balanced socio-economic development of the territories in a federal state. The purpose of the article is to develop the organizational and economic mechanism for innovative development of service sphere The leading approach is an institutional approach that allows to consider the organizational and economic mechanism of maintenance of innovative development of service sphere like purposeful system of government measures that lead to the creation of conditions for more efficient use of assets by business entities operating in the regions, the development of social sectors of the economy to create equal opportunities of citizens and to facilitate the reproduction of the human potential. The paper defines the content of the organizational-economic mechanism of maintenance of innovative development of service spheres, providing coordination of the interests of the federal, regional and municipal governments, different ownership entities, national and regional communities and citizens in order to reduce the level of inter-regional differentiation in the socio-economic conditions and quality of life; gives the characteristic of structure-forming components of the organizational-economic mechanism of maintenance of service spheres’ innovative development (goals, objectives, principles, entities, objects, forms, methods, tools, criteria) at the federal, regional and municipal levels of government; establishes regularities in the maintenance process of innovation development of service spheres. Paper submissions can be useful for specialists of federal and regional authorities, local authorities, ministries, scientists who are interested in the regional economy and management of services sector. Keywords: Innovative Development, Economic Systems, Regional Services Market, Service Spheres Management JEL Classifications: C15, F15, H43